KESESUAIAN LOKASI PENGEMBANGAN KAWASAN INDUSTRI DI KABUPATEN BELITUNG - Bambang Winarno; Prihadi Nugroho (Diponegoro University, 2019)
Industrialization in the region contributes to a prime mover for the economy so that each region competes to provide the most favorable location for the development of the export-oriented main industry. The problem of choosing the location of an industrial estate in Belitung Regency is not ready for infrastructure, RTRW, and industrial regulation. The research question is whether the location has set by the local government in accordance with normative standards/regulations. The purpose of this study is to identify the suitability of the location of Industrial Zone in Belitung Regency. Weighting is used to identify the location and factor analysis used to obtain the main variable in the development of the industrial estate. The findings are the determination of the location of Industrial Zone in Belitung Regency in accordance and fulfill technical standards as regulation, which have determined. The main variable that influences the development of industrial estate in Belitung Regency is land, location, regulation, management, infrastructure, external support, and accessibility factor.